The Role of Na,k-Atpase α Subunit Serine 775 and Glutamate 779 in Determining the Extracellular K(+)And Membrane Potential–Dependent Properties of the Na,k -Pump - Peluffo, R. Daniel (The Rockefeller University Press, 2000)
The roles of Ser775 and Glu779, two amino acids in the putative fifth transmembrane segment of the Na,K -ATPase α subunit, in determining the voltage and extracellular K (+) (K (+) (o)) dependence of enzyme-mediated ion transport, were examined in this study. HeLa cells expressing the α1 subunit of sheep Na,K -ATPase were voltage clamped via patch electrodes containing solutions with 115 mM Na(+) (37°C). Na,K -pump current produced by the ouabain-resistant control enzyme (RD), containing amino acid substitutions Gln111Arg and Asn122Asp, displayed a membrane potential and K (+) (o) dependence similar to wild-type Na,K -ATPase during superfusion with 0 and 148 mM Na(+)-containing salt solutions. Additional substitution of alanine at Ser775 or Glu779 produced 155- and 15-fold increases, respectively, in the K (+) (o) concentration that half-maximally activated Na,K -pump current at 0 mV in extracellular Na(+)-free solutions. However, the voltage dependence of Na,K -pump current was unchanged in RD and alanine-substituted enzymes. Thus, large changes in apparent K (+) (o) affinity could be produced by mutations in the fifth transmembrane segment of the Na,K -ATPase with little effect on voltage-dependent properties of K (+) transport. One interpretation of these results is that protein structures responsible for the kinetics of K (+) (o) binding and/or occlusion may be distinct, at least in part, from those that are responsible for the voltage dependence of K (+) (o) binding to the Na,K -ATPase.